Screening and identification of the dominant antigens of the African swine fever virus - Xu, Zhaoyang; Hu, Yifan; Li, Junbo; Wang, Ancheng; Meng, Xin; Chen, Lingchao; Wei, Jianchao; Tong, Wu; Kong, Ning; Yu, Lingxue; Yu, Hai; Shan, Tongling; et al. (Frontiers in Veterinary Science, 2023)
African swine fever is a highly lethal contagious disease of pigs for which there is no vaccine. Its causative agent African swine fever virus (ASFV) is a highly complex enveloped DNA virus encoding more than 150 open reading frames. The antigenicity of ASFV is still unclear at present. In this study, 35 proteins of ASFV were expressed by Escherichia coli and ELISAs for detection of antibodies against these proteins were developed. p30, p54 and p22 were presented as the major antigens of ASFV, positively reacting with all five clinical ASFV-positive pig sera and 10 pig sera experimentally infected by ASFV. Five proteins (pB475L, pC129R, pE199L, pE184L and pK145R) reacted well with ASFV-positive sera. The p30 induced a rapid and strong antibody immune response during ASFV infection. These results will promote the development of subunit vaccines and serum diagnostic methods against ASFV.